Sustainable materials in concrete railway sleepers: A review of current developments and future prospects - Yee, Jia Jun; Khong, Sheh Ching; Che, Jialing; Tee, Kong Fah; Chin, Siew Choo (Universiti Malaysia Pahang, 2024)
Concretes have been the favoured material to make concrete railway sleepers due to better accessibility and weather compared to their timber counterparts. Railway sleepers are crucial infrastructure and 5% of concrete sleepers fail prematurely. Sleeper failure could result in catastrophic railway accidents. Hence, improvement is needed in the concrete sleeper mixes. Previous literature has identified two methods of improving concrete strength in concrete mixes with wastes, through replacement of concrete constituents or the use of alkali-activated materials. Use of wastes as partial concrete material replacements reduces the volume of concrete materials while alkali-activated material forms a concrete-like compound that eliminates the use of cement. These methods improve the strength performance and sustainability aspects of the concrete. While many studies have been conducted on these two types of sustainable concrete, their application in concrete railway sleepers has not been investigated. Thus, this paper looks to review the two different types of sustainable concretes through some previous literature that has been conducted on its application in concrete railway sleepers as well as those that have yet to be studied. Ultimately, identifying the best sustainable materials for concrete railway sleepers.